2019
DOI: 10.7224/1537-2073.2019-029
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Physical Activity Behavior in Multiple Sclerosis Management

Abstract: Background: Physical activity (PA) is considered the most important non-pharmaceutical intervention for persons living with multiple sclerosis (PwMS). Less than 20% of PwMS are engaging in sufficient amounts of PA to accrue benefits. PA promotion is most effective when combined with additional behavior change strategies (BCS), but this is not routinely done in clinical practice. The purpose of this study is to increase our understanding of current practice and perspectives of health care providers (HCPs) in Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
(20 reference statements)
1
5
0
Order By: Relevance
“…These findings corroborate those of previous studies which have long showed that knowledge does not always translate into action, 28 and further, that MS knowledge is not always associated with self‐efficacy 29 . One qualitative study addressing physical activity behaviours in MS management reported that initiatives to increase engagement with health behaviours in populations such as MS, should also include behaviour change strategies to ensure optimal effectiveness of healthy lifestyle promotion 30 . Strategies may include self‐efficacy assessment, barrier identification and problem solving 31 .…”
Section: Discussionsupporting
confidence: 87%
“…These findings corroborate those of previous studies which have long showed that knowledge does not always translate into action, 28 and further, that MS knowledge is not always associated with self‐efficacy 29 . One qualitative study addressing physical activity behaviours in MS management reported that initiatives to increase engagement with health behaviours in populations such as MS, should also include behaviour change strategies to ensure optimal effectiveness of healthy lifestyle promotion 30 . Strategies may include self‐efficacy assessment, barrier identification and problem solving 31 .…”
Section: Discussionsupporting
confidence: 87%
“…The systematic development of exercise promotion through the patient-provider interaction has evolved extensively through a series of nine articles by our group over the last 5 yr (29)(30)(31)(34)(35)(36)(37)(38)(39) that are buttressed by formative research from others on this topic (40)(41)(42)(43)(44)(45). This line of research was designed using a novel approach whereby we implemented a "bottom-up" strategy focusing on the needs and wants of patients with MS as a foundation (40).…”
Section: Exercise Promotion In Ms Care Via the Patient-provider Inter...mentioning
confidence: 99%
“…The reality of the aforementioned interest by patients in exercise promotion by health care providers is tenuous, unless it aligns with the needs and interests of providers (i.e., neurologists, nurses, physical therapists, and occupational therapists) for undertaking exercise promotion, as the needs and wants of patients might not be feasible for delivery within MS clinical care settings. To that end, other studies recently have been published on the provider's perspective of exercise promotion in MS (34,(43)(44)(45). For example, one study involved semistructured interviews with 44 health care providers that included similar numbers of neurologists, nurse practitioners, physical therapists, and occupational therapists (34).…”
Section: Exercise Promotion In Ms Care Via the Patient-provider Inter...mentioning
confidence: 99%
See 2 more Smart Citations